Understanding First Nations communities’ preparedness, concerns, and strategies for addressing COVID-19 - Final Report ... - Radel, Kylie; Robertson, Jan; Daniels, Carolyn; Miller, Adrian (CQUniversity, 2024)
Australian First Nations communities, including remote communities, are particularly vulnerable to the risks posed by the current COVID-19 pandemic. Pandemic event management falls under national and state all-hazard disaster management arrangements. In most jurisdictions, local governments are responsible for managing events through their Local Disaster Management Groups (LDMG), supported by district and state level groups. This study sought to investigate the capacity of regional and remote local governments of Australian First Nations Communities to develop and deploy pandemic disaster management strategies and plans. The study investigated the preparedness, responses, concerns, and capabilities of communities at the forefront of the pandemic disaster. Findings reported here may assist with future planning for disaster management and risk reduction that incorporates community voices and Indigenous Knowledges and Practices in future regional and remote pandemic policy development and implementation. ...